Fantastic feats and ridiculous records - Phillips, Adam (Tobar Ltd. Worlingham, 2009)
Fantastic Feats and Ridiculous Records by Adam Phillips is a playful compendium that celebrates some of the world$1 (Bs quirkiest, wildest, and most astonishing human achievements. This book dives into a variety of fascinating records, from extreme sports and unusual talents to bizarre inventions and eccentric behaviors. Each record is presented with humor, highlighting the creativity and tenacity behind the unique feats that people have pursued. Packed with fun facts and incredible stories, Phillips$1 (Bcollection provides an entertaining look at human ambition, showcasing the strange yet remarkable things people will do to push boundaries and stans